A new species of Lagis (Polychaeta: Pectinariidae) from Hong Kong - Sun, Yanan; Qiu, Jian-Wen (Zootaxa, 2012)
Lagis crenulatus sp. nov., (Pectinariidae) is described based on specimens collected from an intertidal mudflat in an estu-ary of Hong Kong. The specimens are small, with a body length of 6.4 mm to 15.4 mm. Among a total of 10 describedspecies of Lagis, L. crenulatus sp. nov., and L. abranchiata (Fauvel, 1932) are the only two without thoracic branchiae.Lagis crenulatus sp. nov., can be distinguished from L. abranchiata by having crenulated rather than knobbed margins in the scaphe, and lacking a pair of dorsal elongated pads on the third segment.